COVID-19 pandemic and transgender migrant women in India: Socio-economic vulnerability and vaccine hesitancy - Arun Kumar Acharya; Jennifer Bryson Clark; Sushree Subhalaxmi Behera (Elsevier, 2023)
In India, transgender women, often referred to as hijra or kinnar, remain a marginalized group and encounter interpersonal and structural barriers that subject them to social exclusion, discrimination, lack of access to education and health care, and fewer job opportunities compared with the general population. During the COVID-19 pandemic these disparities were heightened and the livelihood of transgender migrant women were severely hit and disrupted, causing further financial and physical hardship. The present study aims to explore the socio-economic vulnerability faced by these women during the pandemic and the factors that contribute to vaccine hesitancy in order to assist government officials and policy makers in the formulation of more inclusive policies for transgender people. Results indicate that the pandemic has adversely impacted their livelihood as most of them depend on sex work and begging. In order to fulfil their daily needs during the lockdown, they have borrowed loans from multiple sources with a higher interest rates and remain in debt. On vaccination status, only seven out of 43 transgender migrant women have taken one vaccine dose, and the rest are not willing to visit vaccine centres because of societal stigma and discrimination including from healthcare personnel. The study reported that these migrant women suffered intensified social stigma, verbal hostility and transphobia attitudes from healthcare professionals whihc caused panic, fear, anxiety and depression among them, and thus they evade these spaces for further consultation or to obtain any other services. Many of them have decided not to take the COVID-19 vaccine in order to stay away from hostility. Further, the lack of trust in medical professionals is also one of the principal concerns leading to vaccine hesitancy among transgender migrant women. Thus a systemic inclusive healthcare services policy is required to address the factors that may influence the vaccine acceptance among transgender women in India.